SEBARAN GEMPA UTAMA BERDASARKAN MAGNITUDO DAN KEDALAMAN DI WILAYAH MAMUJU DAN SEKITARNYA - Wisnu Erlangga; Mochamad Teguh; Malik Mushthofa; Gunawan Setiadi; Imam Trianggoro Saputro (Jurusan Teknik Sipil, Fakultas Teknik Sipil dan Perencanaan, Universitas Islam Indonesia, 2022)
Sulawesi is one of Indonesia's large islands with a high vulnerability to earthquakes due to its geographical location, which lies between the confluence of tectonic plates and several active faults. The earthquake events' intensity was relatively high with small to large magnitudes. One area recently hit by a large earthquake that caused material losses and casualties was found in Mamuju. Given this condition, it is essential to determine the latest seismicity mitigation in the Mamuju area and its surroundings to look at the distribution of the mainshock based on the magnitude and depth of the earthquake. Earthquakes that occur in a particular area and for a certain period can describe the concentration of earthquake activity. The earthquake data activity used in this study is to find earthquake data for the period 1960-2021, followed by a declustering process which is carried out to separate the mainshock from the aftershocks. Separating the mainshock from the aftershocks is performed using the time window and distance windows criteria. Based on the analysis, it was found that the number of mainshocks that occurred in the Mamuju region was 20.11% of the total earthquake events that occurred (5366 earthquake event data) with a dominance of moderate to large magnitude (4<M<6). Meanwhile, based on the depth of the earthquake, 54.19% of the earthquake event were shallow earthquakes (0 km < D < 60 km). This can be used as a basis for updating existing earthquake maps and for paying attention to the application of earthquake-resistant building regulations and building construction permits in the Mamuju area, considering that the vulnerability to earthquakes in this area is relatively high.